Pyrene-substituted cyclic triimidazole: An appealing and versatile luminescent scaffold for explosive detection. (October 2022) - Formenti, Matteo; Blasi, Delia; Cariati, Elena; Carlucci, Lucia; Forni, Alessandra; Giannini, Clelia; Guidotti, Matteo; Econdi, Stefano; Malpicci, Daniele; Marinotto, Daniele; Lucenti, Elena
Abstract: Two derivatives of cyclic triimidazole and pyrene, namely the blue emitting 3-(pyren-1-yl)triimidazo[1, 2- a :1′, 2′- c :1″, 2″- e ] [1, 3, 5]triazine, TTPyr, and the yellow-orange emitting 11-(pyren-1-yl)triimidazo[1, 2- a :1′, 2′- c :1″, 2″- e ][1, 3, 5]triazine-3, 7-dicarbaldehyde, (CHO) 2 TTPyr, are here exploited for titration experiments with various nitroaromatic energetic hazardous materials and proposed as sensor species for the quantitative detection of explosives. The 565 nm fluorescence of (CHO) 2 TTPyr represents a valid alternative to the TTPyr 420 nm one for analytes absorbing in the blue region. (CHO) 2 TTPyr displays varying degrees of fluorescence quenching towards different nitroaromatics, among which picric acid (PA) detection has the highest sensitive response with a Stern-Volmer quenching constant value equal to 1.25 × 10 4  M −1 and a calculated detection limit of 0.63 ppm. From time resolved photoluminescence experiment, a static mechanism is recognized as responsible for the observed quenching. The hypothesis of a dark complex formation is supported through the isolation and characterization of a TTPyr /PA adduct with 2:1 stoichiometry. Highlights: Two pyrene-susbstituted cyclic triimidazoles exhibit selective detection of nitroaromatic energetic compounds. Time resolved experiments revealed static quenching mechanism with formation of a ground state complex. X-Ray diffraction analysis of the dark complex with picric acid is performed.